Surgical Outcome of Right Ventricular Outflow Tract Reconstruction Using Bicuspid Pulmonary Valve in Tetralogy of Fallot Repair: A Single Centre Experience (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Tetralogy of Fallot (TOF) is one of the most common congenital cardiac defect. In patients with small PV annulus, it has to be augmented to certain diameter by cutting annulus. In these cases, transannular patch is used free PR is inevitable. Free PR with transannular patch ultimately leads to RV dilatation, dysfunction, arrhythmia and failure with time. Monocuspid reconstruction of PV is commonly practiced in many centers but its long-term outcome is poor though it helps to achieve a less stormy ICU course. Modified monocusp or bicuspid PV reconstruction is a good choice where 0.1mm PTFE patch is used.Objectives: We are presenting the results of bicuspid PV reconstruction using a 0.1mm PTFE patch as a method of RVOT reconstruction in repair of TOF with transannular patch.Methods: A total, 42 patients diagnosed as TOF were treated from January 2016 to October 2020. Age range 18 months to 35 years, weighing 10 kg to 70 kg. 38 patients had TOF, 4 had DORV with PS. The transannular patch was followed by implantation of a 0.1-mm PTFE modified monocusp valve using posterior fixation.Results: Among total patients 28 were male and 14 were female. Mean age 9.58±5.6 yrs. Bypass time was 187±31 min, cross-clamp time 123.63±25.42 min. Out of 42 patients, PR gradient was trivial in 7(16.67%), mild in 31(73.1%), moderate in 4(9.52%) patients. First, a follow-up echocardiogram revealed no significant deterioration of PR gradient. ICU stay was 89±32.6 hours and mean hospital stay 11.48±2.1 days.Conclusion: Initial results using a transannular patch with a modified monocusp valve to repair the outflow tract in cases of Tetralogy of Fallot were excellent. There were only a slight pressure gradient and mild regurgitation in most of the cases.DS (Child) H J 2020; 36(2): 114-119